2012
DOI: 10.1007/s00431-012-1679-7
|View full text |Cite
|
Sign up to set email alerts
|

Arterial stiffness is not increased in teens with early uncomplicated type 1 diabetes mellitus

Abstract: People with type 1 diabetes mellitus are at an increased risk of cardiovascular mortality. Studies comparing arterial stiffness between subjects with type 1 diabetes and nondiabetic controls have provided controversial findings.We investigated brachial–ankle pulse wave velocity (baPWV) in 87 teenagers with type 1 diabetes mellitus and in 21 matched healthy controls. Our data show that baPWV was not increased in teenagers after a median illness of 5 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 10 publications
1
11
1
Order By: Relevance
“…There are a number of cross sectional studies of arterial stiffness in youth with T1D (Haller et al, 2004, Heilman et al, 2009, Palombo et al, 2011, Urbina et al, 2010, Yu et al, 2012) but few prospective studies (Dabelea et al, 2013). Two prospective studies in non-diabetic adults found that the presence of metabolic syndrome (a cluster of CVD risk factors) at baseline was associated with faster progression of arterial stiffness over time (Safar et al, 2006, Tomiyama et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of cross sectional studies of arterial stiffness in youth with T1D (Haller et al, 2004, Heilman et al, 2009, Palombo et al, 2011, Urbina et al, 2010, Yu et al, 2012) but few prospective studies (Dabelea et al, 2013). Two prospective studies in non-diabetic adults found that the presence of metabolic syndrome (a cluster of CVD risk factors) at baseline was associated with faster progression of arterial stiffness over time (Safar et al, 2006, Tomiyama et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Another study found higher PWV among 72 children with T1DM with an average age of 12.3 ± 1.6, HbA1c 8.6 ± 1.9%, and diabetes duration of 3.9 ± 2.6 years when compared to 77 HC. In a different study that used brachial-ankle pulse wave velocity as an index of arterial stiffness, no difference was seen among 87 children with T1DM with median HbA1c 9.1% and duration of diabetes 5.1 years compared to 21 HC [ 21 ]. Similar results were also seen in a recent study with 199 youths with T1DM compared to 178 HC [ 22 ].…”
Section: Manifestations Of Subclinical Cardiovascular Diseasementioning
confidence: 99%
“…111 Studies that found no increase in arterial stiffness in T1DM used nonstandard methods of assessing arterial stiffness that have not been validated in youth. 112,113 One large study of adolescents with T2DM (n=195) demonstrated increased arterial stiffness (lower brachial distensibility, higher augmentation index and pulse-wave velocity) in adolescents with T2DM compared with either lean or obese control subjects. 114 The only interventional study showed a trend for improvement in augmentation index with statin administration in youth with T1DM (n=51).…”
mentioning
confidence: 99%